Formal concept analysis : 14th International Conference, ICFCA 2017, Rennes, France, June 13-16, 2017, Proceedings /: 14th International Conference, ICFCA 2017, Rennes, France, June 13-16, 2017, Proceedings. (2017) - Unknown
No abstract available